2021
DOI: 10.1186/s41065-021-00196-8
|View full text |Cite
|
Sign up to set email alerts
|

Dynamic co-expression modular network analysis in nonalcoholic fatty liver disease

Abstract: Background Nonalcoholic fatty liver disease (NAFLD) is the most common chronic liver disease affecting people’s health worldwide. Exploring the potential biomarkers and dynamic networks during NAFLD progression is urgently important. Material and methods Differentially expressed genes (DEGs) in obesity, NAFL and NASH were screened from GSE126848 and GSE130970, respectively. Gene set enrichment analysis of DEGs was conducted to reveal the Gene Ontol… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

0
2
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
7

Relationship

0
7

Authors

Journals

citations
Cited by 9 publications
(4 citation statements)
references
References 46 publications
(50 reference statements)
0
2
0
Order By: Relevance
“…Some of them have been linked to liver-related diseases. For example, Zheng et al identified CDKN1A as a potential key regulator of NASH via dynamic network analysis and dynamic gene coexpression module analysis [ 18 ]. Furthermore, studies have shown that the circRNA MAN2B2 promotes the proliferation of hepatoma cells through the miRNA-217/MAPK1 axis [ 19 ], which indirectly supports our results.…”
Section: Discussionmentioning
confidence: 99%
“…Some of them have been linked to liver-related diseases. For example, Zheng et al identified CDKN1A as a potential key regulator of NASH via dynamic network analysis and dynamic gene coexpression module analysis [ 18 ]. Furthermore, studies have shown that the circRNA MAN2B2 promotes the proliferation of hepatoma cells through the miRNA-217/MAPK1 axis [ 19 ], which indirectly supports our results.…”
Section: Discussionmentioning
confidence: 99%
“…Gene expression matrix of GSE130970 (named as NAFLD dataset), based on GPL16791 (Illumina HiSeq 2500), were downloaded as transcripts Per Kilobase per Million mapped reads (TPMs) and were subsequently transferred to gene symbol from Entrez id. Liver biopsy samples were categorized into two groups: those with a NAFLD activity score (NAS) ≥ 5, referred to as the NAFLD group, and those with NAS < 5, considered as the control group 12 . Gene expression data from GSE115574, GSE14975, and GSE63067 were used as validation datasets.…”
Section: Methodsmentioning
confidence: 99%
“…CDKN1A correlated with age, CYCS with lobular inflammation and cytological ballooning grade, and CXCL10 with steatosis grade. Importantly, THY‐1 was the most relevant gene correlated with fibrosis stage 12 …”
Section: Introductionmentioning
confidence: 97%
“…Importantly, THY-1 was the most relevant gene correlated with fibrosis stage. 12 Thy-1 is a highly glycosylated, glycosylphosphatidylinositol (GPI)-anchored membrane protein. 13 Its expression is restricted to fibroblasts, neurons, activated microvascular endothelial cells, glomerular cells, a subpopulation of haematopoietic stem cells, and…”
Section: Introductionmentioning
confidence: 99%